Penerapan PSO Over Sampling Dan Adaboost Random Forest Untuk Memprediksi Cacat Software - Richky Faizal Amir; Irwan Agus Sobari; Rousyati Rousyati (Indonesian Journal on Software Engineering (IJSE), 2020)
Abstract: The dataset of software metrics, in general, are not balanced (Imbalanced). Class imbalance in Dataset can reduce the performance of software defect prediction models, because it tends to produce majority class predictions from minority classes, the dataset used in this study uses the National Aeronautics and Space Administration (NASA) Metrics Data Program (MDP), dataset From Stages Pre-processing proposed the Particle Swarm Optimization (PSO). method to overcome the problem of attributes in the training data and the Random Over Sampling (ROS) Resampling method. to deal with class imbalances. This study proposes that the Random Forest method combined with Adaboost can estimate the level of disability of software through training data. The results of this study indicate that the Resampling + Adaboost + Random Forest algorithm can be used to predict software defects with an average accuracy of 94.70% and a value of AUC 0.939. While the PSO + Random Forest algorithm only has an average accuracy of 89.60% and AUC 0.636 the difference in the accuracy of the two models is 5.10% and AUC 0.303. Statistical tests show that there is a significant influence between the proposed model and the Random Forest model with a p-value (0.036) smaller than the alpha value (0.05), which means there is a significant difference between the two models.Keywords: Imbalanced Class, Resample, Particle Swarm Optimization, Random Forest, Adaboost, Software DefectAbstrak: Dataset dari software matrik secara umum bersifat tidak seimbang (Imbalanced). Ketidak seimbangan kelas yang ada dalam dataset dapat menurunkan kinerja model prediksi cacat software, karena cenderung menghasilkan prediksi kelas mayoritas dari kelas minoritas. Dataset yang digunakan pada penelitian ini menggunakan dataset National Aeronautics and Space Administration (NASA) Metrics Data Program (MDP). Dari tahapan pra pemrosesan diusulkan metode Particle Swarm Optimization (PSO) untuk mengatasi masalah attribute pada data training dan metode Resampling Random Over Sampling (ROS). untuk menangani ketidak seimbangan kelas. Penelitian ini mengusulkan metode Random Forest yang dikombinasikan dengan Adaboost dapat mengestimasi tingkat kecacatan suatu Software melalui data training, Dari Hasil penelitian ini menunjukan bahwa algoritma Resampling+Adaboost+Random Forest dapat digunakan untuk memprediksi cacat software dengan rata-rata akurasi 94,70% dan nilai AUC 0,939. Sementara algoritma PSO+Random Forest hanya memiliki rata-rata akurasi 89,60% dan AUC 0,636 perbedaan akurasi dari kedua model tersebut 5,10% dan AUC 0,303. Uji statistik menunjukan bahwa adanya pengaruh yang signifikan antara model usulan dengan model Random Forest dengan nilai p (0,036) lebih kecil dari nilai alpha (0,05) yang artinya terdapat perbedaan yang siginifkan antara kedua model.Kata kunci: Imbalanced Class, Resample, Particle Swarm Optimization, Random Forest, Adaboost, Kecacatan Software